Prevalence and severity of Periodontal disease among institutionalized elderly in Baghdad-Iraq (Mustansiria Dental Journal, 2005)
This research analyzes data {rom dentate institutionalized elderly in Baghdad city .The study population comprised (100) dentate elderly ranging in age from 50-100 years27( males and 28 females) .Results showed that Prevalence of gingivitis was 100%among the elderly in both sexes and that the severity is higher among females for score 3and 2 of plaque index .